Reduced Activity of Nitrate Reductase Under Heavy Metal Cadmium Stress in Rice: An in silico Answer - Singh, Prerna; Singh, Indra; Shah, Kavita (Frontiers in Plant Science, 2019)
Cadmium is a well known toxic heavy metal, which has various detrimental effects on plant system. In plants an important enzyme involved in the production of nitric oxide, nitrate reductase, is also affected by cadmium toxicity. According to many workers cadmium has an inhibitory effect on nitrate reductase activity. Similar effect of cadmium was found in our study where an inhibitory effect of cadmium on nitrate reductase activity was noted. However the mechanism behind this inhibition has not been explored. With the help of homology, 3-D structure of rice- nitrate reductase is modeled in this study. It’s binding with nitrate, nitrite and cadmium metal in silico has been explored. The bonds formed between the enzyme-substrate complex, enzyme-cadmium and differences in interactions in presence of cadmium has been studied in detail in silico. The present study should help in understanding the modeled structure of rice- nitrate reductase in 3-D which may in turn guide enzyme related studies in silico. The present study also provides an insight as to how cadmium interacts with nitrate reductase to alter the enzyme activity.